2019
DOI: 10.1186/s12889-019-7370-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an electronic medium delivery of warfarin education in a low income, minority outpatient population: a pilot intervention study

Abstract: Background Warfarin is classified as a high-alert medication for ambulatory healthcare and safe guards for high-alert medications are necessary, including the practice of mandatory patient education. The high cost of hospitalizations related to adverse events combined with the average bleeding event rate of 7–8% in spite of routine patient education, suggests the importance of new approaches to standardized health education on warfarin. We sought to evaluate the impact of a warfarin educational vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
0
6
0
4
Order By: Relevance
“…Based on research evidence and prior experiences, the tablet application, the e-learning platform, and the website were implemented to strengthen health literacy, encourage guideline fidelity, and provide a subsequent change in antibiotic use habits for ARTI in German primary care. Prior studies used tablet computers to specifically disseminate health literacy in adults [30][31][32], for self-management programs for chronic diseases [33], diagnostics [34,35], interventions for parents and children [36][37][38][39][40], coping strategies after diverse surgeries [8,41], or as tracking functions for aims of weight reduction [42] and general fitness [43,44]. However, the findings of this study demonstrate a variety of challenges and a reluctance toward using digital information tools in German primary care practices for both patients and health professionals.…”
Section: Overviewmentioning
confidence: 85%
“…Based on research evidence and prior experiences, the tablet application, the e-learning platform, and the website were implemented to strengthen health literacy, encourage guideline fidelity, and provide a subsequent change in antibiotic use habits for ARTI in German primary care. Prior studies used tablet computers to specifically disseminate health literacy in adults [30][31][32], for self-management programs for chronic diseases [33], diagnostics [34,35], interventions for parents and children [36][37][38][39][40], coping strategies after diverse surgeries [8,41], or as tracking functions for aims of weight reduction [42] and general fitness [43,44]. However, the findings of this study demonstrate a variety of challenges and a reluctance toward using digital information tools in German primary care practices for both patients and health professionals.…”
Section: Overviewmentioning
confidence: 85%
“…Instead, perceptions about innovation characteristics were more dominant, leading to a preference for more familiar and traditional solutions. Prior studies also used multimedia approaches to provide information in a digitally enhanced manner and offered printed information, videos, or individualized risk assessments [ 31 , 32 ]. In contrast to our findings, those studies showed significant effects of the use of tablets as educational devices for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pasien dengan TTR rendah (<65%) berisiko lebih tinggi terhadap hasil yang buruk. Tercapainya nilai TTR yang tinggi dan kecilnya angka kejadian merugikan sebagai bukti dari pasien memahami pendidikan dan meningkatnya kepatuhan dalam terapi warfarin 13,19,23 . Sama halnya dengan pemberian video pendidikan warfarin, pendidikan dalam sebuah program PSM ini juga memberikan kepatuhan yang tinggi karena dapat diakses kapan saja.…”
Section: Situs Web Edukasi Daringunclassified
“…Penelitian yang dilakukan di Texas, Amerika Serikat ini memperlihatkan median skor tes pengetahuan dan kepatuhan pasien setelah menonton video pendidikan lebih tinggi (dengan skor 12) jika dibandingkan dengan sebelum menonton video pendidikan (dengan skor 10). Penilaian pengetahuan dan kepatuhan pasien menggunakan kuesioner AKA yang mengandung 29 pertanyaan dengan kemungkinan skor tertinggi 12 dan terendah 013 . Peningkatan skor tes pengetahuan juga dilaporkan oleh penelitian Moore et al tahun 2015 di Amerika Serikat untuk pasien yang diberikan intervensi pendidikan dan konseling mengenai warfarin dalam bentuk video dari 60,8% menjadi 74,3% dibandingkan dengan pasien perawatan biasa dan menerima konseling oral yaitu dari 60,5% menjadi 71,3%15 .…”
unclassified
See 1 more Smart Citation